Genetic resources and indigenous peoples: the thesis of indigenous cultural property in the face of public domain - Millaleo Hernández, Salvador (Acta Bioethica, 2019)
The article analyzes the position of indigenous peoples and their ethical-political foundations regarding due protection of genetic resources linked to traditional knowledge. This position has claimed cultural property of a collective nature with respect to these resources, differing explicitly from the solution that understands that these should fall into the public domain. For this purpose, a conception of property with other determination factors, compared to Western property, is outlined. The position of indigenous peoples has been widely and consistently sustained for decades and has come to be included in the international human rights regime, through the UN Declaration on the Rights of Indigenous Peoples; but, in the negotiations at WIPO, it has not managed to break past its critics and the interests of companies and states.